Schools as agents of cultural transmission and social control - Omar LAOUIRA (Revue des Sciences Humaines)
During the development of sociology of education, there have been a move from macro questions of education and social change, and from the notion of input-output of people in education, to a greater concern with problems of curriculum change, teacher-pupil relationship, the formation of pupil identities, in other words to the complex question of how culture is transmitted through schools. This shift is precisely dated from the publication of Knowledge and control (1971), edited by M.F.D Young (Williamson, 1979, P10).